Correlated risks: A conflict of interest between insurers and consumers and its resolution - Patrick Eugster; Peter Zweifel (University of Zurich, Socioeconomic Institute, 2006)
This contribution starts out by noting a conflict of interest between consumers and insurers. Consumers face positive correlation in their assets (health, wealth, wisdom, i.e. skills), causing them to demand a great deal of insurance coverage. Insurers on the other hand eschew positively correlated risks. It can be shown that insurance contributes to a reduction of their asset volatility only if unexpected deviations of payments from expected value correlate negatively across lines of insurance. Analyzing deviations from trend in aggregate insurance payments, one finds the following for the United States and Switzerland. Private U.S. but not Swiss insurance has a hedging effect for consumers, while both social insurance schemes expose consumers to excess asset volatility. In the insurance systems of both countries, the private component fails to offset deviations in the social component (and vice versa). As to the supply of insurance, cointegration analysis indicates the absence of common trends. Therefore, insurance companies could offer combined policies to the benefit of consumers, hedging their underwriting risks both domestically and internationally.
Keywords: G22; G15; G11; D14; C22; 330; Insurance; Portfolio Theory; International Diversification; Combined Contracts; Versicherung; Verbraucher; Risikomodell; Risikomanagement; Portfolio-Management; Schätzung; USA; Schweiz